2020
DOI: 10.1111/ijcs.12571
|View full text |Cite
|
Sign up to set email alerts
|

The links between job insecurity, financial well‐being and financial stress: A moderated mediation model

Abstract: This study proposed a nuanced approach to the association between job insecurity and financial stress by examining whether financial well‐being mediates the established association. In addition, we examined whether the association between the job insecurity and financial stress, through financial well‐being, is moderated by income. For this study, we conducted a path analysis using 1,145 survey respondents. Results revealed a significant relationship between the job insecurity and financial stress and a partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 41 publications
(78 reference statements)
9
59
0
1
Order By: Relevance
“…Researchers have realized that job insecurity has increased stress among workers regarding their health as well as their lives (Soelton, Amaelia & Prasetyo, 2020). Job insecurity may also pose financial stress among employees (Choi, Heo, Cho, & Lee, 2020). According to some experts (Mukhtar, 2020;Korman and Mujtaba, 2020), the COVID-19 outbreak has created numerous mental health issues in Asian countries like Pakistan.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have realized that job insecurity has increased stress among workers regarding their health as well as their lives (Soelton, Amaelia & Prasetyo, 2020). Job insecurity may also pose financial stress among employees (Choi, Heo, Cho, & Lee, 2020). According to some experts (Mukhtar, 2020;Korman and Mujtaba, 2020), the COVID-19 outbreak has created numerous mental health issues in Asian countries like Pakistan.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…Hence, it is important to highlight each employee's emotional reactions in response to job insecurity due to COVID-19 to provide some practical solutions to overcome their stress. ISSN 2162-3058 2021 Financial stress amongst employees may make job insecurity a more agonizing experience, which in return intensifies financial stress (Choi, Heo, Cho, & Lee, 2020). Huge unemployment persists in Pakistan (Ahmed, 2020), which may further trigger job insecurity perceptions in the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Based on responses from more than 7,700 households and 19,000 family members in Italy, Giannetti et al (2014) reported that job insecurity could lead to financial distress (or stress), which was more pronounced for those people who were employed on a parttime basis. The relationship between job insecurity and financial stress was found to be partially mediated by FWB (Choi et al, 2020). Perceived job insecurity refers to an individual's perception of the threat of losing his or her job (Choi et al, 2020;De Cuyper & De Witte, 2006;Haynie et al, 2016).…”
Section: Job Insecurity and Employees' Fwbmentioning
confidence: 96%
“…The relationship between job insecurity and financial stress was found to be partially mediated by FWB (Choi et al, 2020). Perceived job insecurity refers to an individual's perception of the threat of losing his or her job (Choi et al, 2020;De Cuyper & De Witte, 2006;Haynie et al, 2016). Perceived job insecurity can be influenced by personal factors such as gender, age, education level, and personality traits and macroeconomic factors such as unemployment rate, consumer price index, gross domestic product (GDP), and government expenditures.…”
Section: Job Insecurity and Employees' Fwbmentioning
confidence: 99%
See 1 more Smart Citation